Distribution of gas hydrates on continental margins by means of a mathematical envelope: A method applied to the interpretation of 3D Seismic Data. (23rd January 2014) - Bale, Sean; Alves, Tiago M.; Moore, Gregory F.
<x xml:space="preserve">Abstract</x> [1] A 3D seismic volume from the Nankai Trough accretionary wedge (SE Japan) is used to evaluate the subsurface distribution of gas hydrates as a function of structural and stratigraphic complexity, variable heat flow patterns and the presence of subsurface fluid conduits. Eleven equations were modified for depth, pressure, and temperature, modeled in 3D, and compared with the distribution of Bottom‐Simulating Reflections (BSRs) offshore Nankai. The results show that the equations produce overlapping—and thus potentially consistent—predictions for the distribution of BSRs, leading us to propose the concept of a "BSR Stability Envelope" as a method to quantify the subsurface distribution of gas hydrates on continental margins. In addition, we show that the ratio (R) between shallow and deep BSRs of seven subenvelopes, which are defined by BSR stability equations, indicates local gas hydrate equilibrium conditions. Values of R < 1 relate to cooler regions, whereas when R > 1 the majority of BSRs are located in warmer structural traps. The method in this paper can be used to recognize any divergence between observed and theoretical depths of occurrence of BSRs on 3D or 4D (time lapse) seismic volumes. In the Nankai Trough, our results point out for equilibrium conditions in BSRs located away from the Megasplay Fault Zone and major thrust faults. This latter observation demonstrates the applicability of the method to: (a) the recognition of subsurface fluid conduits and (b) the prediction of maximum and minimum depths of occurrence of gas hydrates on continental margins, under distinct thermal and hydrologic conditions.